2018
DOI: 10.3389/fmicb.2018.00651
|View full text |Cite
|
Sign up to set email alerts
|

How Does Salinity Shape Bacterial and Fungal Microbiomes of Alnus glutinosa Roots?

Abstract: Black alder (Alnus glutinosa Gaertn.) belongs to dual mycorrhizal trees, forming ectomycorrhizal (EM) and arbuscular (AM) root structures, as well as represents actinorrhizal plants that associate with nitrogen-fixing actinomycete Frankia sp. We hypothesized that the unique ternary structure of symbionts can influence community structure of other plant-associated microorganisms (bacterial and fungal endophytes), particularly under seasonally changing salinity in A. glutinosa roots. In our study we analyzed bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 89 publications
4
49
0
Order By: Relevance
“…They also found that the sampling season was not influencing the biodiversity. Seasonality did not appear to be an essential factor in shaping endophytic microbial communities in saline soils also from other studies (Thiem et al, 2018).…”
Section: Bacterial and Fungal Communities Associated With Roots And Rsupporting
confidence: 57%
See 1 more Smart Citation
“…They also found that the sampling season was not influencing the biodiversity. Seasonality did not appear to be an essential factor in shaping endophytic microbial communities in saline soils also from other studies (Thiem et al, 2018).…”
Section: Bacterial and Fungal Communities Associated With Roots And Rsupporting
confidence: 57%
“…Kearl et al (2019) isolated bacteria from halophytes (Salicornia and Allenrolfea) and observed that there were different populations in samples collected at different times of the year, with a majority of the genera, however, present independent of when the samples were collected. Thiem et al (2018) analysed the community structure of plant-associated endophytes of Alnus glutinosa, that is a dual mycorrhizal tree that forms ectomycorrhizal (EM) and arbuscular (AM) root structures, and can typically associate also with nitrogen-fixing actinomycetes. The authors sampled the plant's root microbiome present at two forest test sites (saline and non-saline).…”
Section: Bacterial and Fungal Communities Associated With Roots And Rmentioning
confidence: 99%
“…Investigations conducted in different monospecific forests presenting the same age, the same initial substrate and climatic conditions, showed that the effect of tree species on the composition of soil fungal communities explained up to 47% of the variation observed while the effects of C, N, P and pH were insignificant (Urbanová et al, 2015). However, in New Caledonia mangroves, salinity is also an important factor shaping tree distribution, higher salinity being associated with A. marina (Deborde et al, 2015), and might impact directly or indirectly plant associated fungal communities (Thiem et al, 2018). Moreover, Fungi tended to be tree-specific (Zhou and Hyde, 2001;Buée et al, 2011) even in the case of mangrove ecosystems where the aerial and intertidal parts of A. marina or R. stylosa exhibited different fungal communities (Arfi et al, 2012a).…”
Section: The Influence Of Tree Species On Microbial Communities Compomentioning
confidence: 99%
“…There are reports claiming that each year around 1–2% of fertile soils are being degraded worldwide due to salinity [6] . It has also been forecasted that in the next 35 years, about 50% of the land on earth will suffer due to various degrees of salinity [7] . Additionally, data indicates that in past few decades the annual cost of salt-induced land degradation in irrigated areas was estimated to be US$ 27.3 billion [8] .…”
Section: Introductionmentioning
confidence: 99%